Penyuluhan Keluarga Berencana Pada Pasangan Usia Subur Kelurahan Biraeng dan Kelurahan Bonto Kio - Qamarya, Nurul; Nawangwulan, Kurniati; Agustang, Andi; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Family planning counseling is an activity of delivering information to improve the knowledge, attitudes and behavior of families and communities in order to realize quality families. Fertile Age Couples (PUS) are married couples whose wives are between 20 and 45 years old or married couples whose wives are less than 20 years old and have menstruated or whose wives are more than 45 years old, but still menstruate. The aim is to prevent pregnancy in couples of childbearing age who are legally bound. This PkM method is health promotion or counseling by providing information. In the target of health counseling activities carried out on couples of childbearing age in Bonto Kio Village and Biraeng Village, Minasatene District, Pangkajene Islands Regency. The final result seen from this counseling activity is that most participants realize and understand the prevention of pregnancy by using contraceptive methods.